Heterogeneity and Volatility Puzzles in International Finance - Li, Tao; Muzere, Mark L. (Journal of Financial and Quantitative Analysis, 2010)
We develop an equilibrium model in a 2-country, 2-good, pure exchange economy in which investors with logarithmic utility functions have heterogeneous beliefs about exogenously given output or endowment processes. We obtain closed-form representations of real exchange rates and of stock prices. We show that heterogeneous beliefs together with heterogeneous preferences make the volatility of real exchange rates and of stocks exhibit some properties that have been well documented in the empirical literature. These properties include the high volatility of both real exchange rates and stocks compared with that of economic fundamentals, the high correlation of stocks during periods of volatile markets. The model can also generate the clustering of the volatility of foreign exchange rates and stocks if the differences of beliefs are clustering.